Analysis of information literacy competencies assessment studies submitted to the University of the Philippines School of Library and Information Studies (2002-2016) - Domingo, Angelee S. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Information literacy is a fundamental skill and forms the foundation of an individual for lifelong learning and essential for adapting in today's modern society. Technology is rapidly growing, thus, information literacy skills are vital in order to adjust to this kind of environment full of plethora of information. It includes recognizing when information is needed and being able to efficiently locate, correctly evaluate, effectively use, and clearly link information in several formats. Students today face a daily explosion of information resources and the challenge of using these resources effectively and responsibly.